Covid-19 Pandemic: Assessment of Its Impact and Insurability of Pandemic Risks in The Nigerian Insurance Business - Omotayo Johncally, Abere; Toyin Shafau, Saka (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
Coronavirus is a virus whose genome consists of a single strand of ribonucleic acid. The timing and the global environment (China) from which COVID-19 originated from has made its spread faster than expected because China had 739 international air travel routes and 51 million people used to travel between China and other countries before the disease outbreak. Therefore, there is a need to investigate the impacts and the mortality rate of this deadly disease in order to consider its insurability. The specific objective of this research is to analytically examine factors affecting the insurability of pandemic risks in the Nigerian insurance business within the specified time frame. Different methods/strategies of investigations were conceived to gather data/materials related to the study in order to have comprehensive knowledge of the subject matter. The two statistical tools used are descriptive and inferential. Kaplan Meier Model was used to carry out the hazard estimate based on the computation arrived at using the Microsoft Excel package. This study analyzed 167 467 cases reported/observed within seventeen (17) months in Nigeria (Feb 2020-June 2021). The geographical location of this research is global. It is not limited to Nigeria alone but special attention was paid to cases in Nigeria to consider the insurability of pandemic risks by the Nigerian insurers. 0.5 connotes equal chance of death and survival. As the value moves closer to 1 from 0.5, the probability risk of death is becoming more certain and vice versa. It is clear from the analysis that as months passed by, the estimated figures began to increase showing that more deaths were being recorded. The lockdown and other safety measures adopted to fight COVID-19 disrupted economic recovery, affected financial markets/services, and in turn increased insurance claims. The pandemic impacts on the global insurance markets have been largely affected as a result of weaker premium growth prospects, capital market volatility, asset risks, and so on. In times of crisis, losses come as well as opportunities. This study suggested how identified negative impacts of COVID-19 could be minimized while strategizing to maximize the opportunities therein. It also showed analytically how high mortality risk poses threat to the insurability of pandemic risks.